Protozoa evolution in single-flow continuous culture and Rusitec fermenters fed high-forage diets - Moumen A.; Yáñez Ruiz D.R.; Carro M.D.; Molina Alcaide E. (Nutritional and foraging ecology of sheep and goats, 2009)
The aim of this study was to investigate the evolution of protozoa numbers in two types of rumen-simulating fermenters [single-flow continuous culture fermenters (SFCCF) and semi-continuous flow fermenters (Rusitec)] receiving high-forage diets. Ruminal inoculum from sheep and goat were used in SFCCF trials, whereas only sheep inoculum was used for Rusitec fermenters. In both systems incubation trials were conducted for 14 days by following the methodologies usually utilized in each of the participant laboratories. The flow through all fermenters was maintained by continuous infusion of artificial saliva at a dilution rate of 5.3%/h (1.3 per day). Retention time of solid digesta was 19 and 48 h in SFCCF and Rusitec fermenters, respectively. Protozoa numbers decreased (P < 0.001) rapidly with time from the first day after inoculation in all fermenters. The decrease was more pronounced in SFCCF than in Rusitec over the first 2 days post-inoculation, with values dropping to 17.8 and 33.0% of those on day 0 in SFCCF and Rusitec, respectively. In contrast, on day 4 SFCCF maintained greater protozoa numbers than Rusitec fermenters (8.75 × 104 and 4.1 × 104 per ml, respectively). Protozoa completely disappeared after 7 days in SFCCF, whereas they were present in Rusitec fermenters even 14 days after inoculation (1.0 × 104 per ml). Holotrich protozoa disappeared completely in SFCCF by the second day after inoculation, but they were maintained in Rusitec fermenters for 12 days. The better ability of Rusitec fermenters than that of SFCCF to maintain protozoa might be related to the greater retention time of solid digesta in the Rusitec system.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)